Comparative analysis of business conditions in EU countries by doing business rating - Riepina, I.; Yakusheva, N. (Baltic International Academy, 2019)
В роботі проаналізовано рівень розвитку бізнесу в країнах Євросоюзу за допомогою рейтингу легкості ведення бізнесу Doing Business. Складено рейтинг країн ЄС, які мають сприятливе бізнес-середовище. Зроблено висновки про покращення умов ведення бізнесу, оскільки Євросоюз надає підприємцям єдиний ринок, сприятливі умови для бізнесу та єдину інформаційну базу. // The paper analyzes the level of business development in the European Union using the rating of ease of doing business Doing Business. Make a rating of EU countries that have a favorable business environment. It is concluded that the business environment has improved, as the European Union provides entrepreneurs with a single market, favorable business conditions and a single information base.
Keywords: малий бізнес; рейтинг Doing Business; умови ведення бізнесу; small business; Doing Business rating; business conditions